Mixed Culture of Yeast and Lactic Acid Bacteria for Low-Temperature Fermentation of Wheat Dough - Wiktoria Liszkowska; Ilona Motyl; Katarzyna Pielech-Przybylska; Urszula Dziekońska-Kubczak; Joanna Berłowska (Molecules)
There is growing interest in low-temperature food processing. In the baking industry, low-temperature fermentation improves the production of natural aroma compounds, which have a positive impact on the sensory profile of the final product. The aim of this study was to develop a yeast–lactic acid bacteria starter culture that effectively ferments wheat dough at a temperature of 15 °C. The microorganisms were selected based on their enzymatic activity and ability to grow at low temperature. The fermentation activity of the yeast and mixed cultures was assessed enzymatically. The biosynthesis of volatile organic compounds was quantified using the HS-GC-MS technique. Samples fermented by S. cerevisiae D3 were characterized by the highest concentration of volatile organic compounds, especially esters. The addition of lactic acid bacteria increased not only the biosynthesis of volatile organic compounds but also the productivity of carbon dioxide during dough fermentation. Based on both dough expansion and the profile of volatile organic compounds, a mixed culture of S. cerevisiae D3 and L. brevis B46 was selected as the most effective starter for low-temperature fermentation.